2023
DOI: 10.1126/science.ade6289
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide genetic screen uncovers determinants of human pigmentation

Abstract: Skin color, one of the most diverse human traits, is determined by the quantity, type, and distribution of melanin. In this study, we leveraged the light-scattering properties of melanin to conduct a genome-wide screen for regulators of melanogenesis. We identified 169 functionally diverse genes that converge on melanosome biogenesis, endosomal transport, and gene regulation, of which 135 represented previously unknown associations with pigmentation. In agreement with their melanin-promoting function, the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 80 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Structural variants (SVs) are also a significant source of genomic variation that involve changes in multiple or even thousands of bases that can have a significant impact on the genome (Alkan et al, 2011). Therefore, SVs may also serve as tion by regulating the pH of melanosomes (Bajpai et al, 2023). This study provides new evidence to improve the genetic map of melanin synthesis, and further analysis of the molecular evolutionary process of these genes will provide more information on the evolution of human skin colour.…”
Section: Discussionmentioning
confidence: 91%
“…Structural variants (SVs) are also a significant source of genomic variation that involve changes in multiple or even thousands of bases that can have a significant impact on the genome (Alkan et al, 2011). Therefore, SVs may also serve as tion by regulating the pH of melanosomes (Bajpai et al, 2023). This study provides new evidence to improve the genetic map of melanin synthesis, and further analysis of the molecular evolutionary process of these genes will provide more information on the evolution of human skin colour.…”
Section: Discussionmentioning
confidence: 91%
“…Inhibiting MITF transcription results in decreased melanin synthesis ( Yuan et al, 2016 ). TYR is the rate-limiting enzyme and key enzyme for melanin synthesis ( Bajpai et al, 2023 ). Cho et al (2021) conducted molecular analysis of TYR and found that abnormal transcription of TYR leads to the recessive white feather phenotype.…”
Section: Discussionmentioning
confidence: 99%